Linearly concentrating solution favors efficient and precise determination of critical pitting chloride concentration - Jia-Yi Gao; Yang Bai; Cheng-Ping Ye; Xian-Zong Wang (Electrochemistry Communications)
The critical pitting chloride concentration (CPCC) is an essential parameter for the safe service of structural alloys that sensitive to pitting corrosion. Precise lacking and time-consuming frustrates the traditional method (multiple tests), i.e., applies various solutions with different concentrations and then gradually approaches the real CPCC. Herein, a novel method (single test) was proposed to efficiently and precisely positioning CPCC, i.e., linearly increasing chloride concentration that realized by a peristaltic pump with a high precision drip rate of μL/min. Moreover, a non-linear sensitivity of CPCC to concentrating rate of chloride ion was revealed on CoCrFeNiAlx alloys and the possible mechanism is discussed.